Evidence Mapping Based on Systematic Reviews of Cognitive Behavioral Therapy for Neuropathic Pain. (18th March 2023) - Li, Conghui; Hou, Weiqian; Ding, Dongfang; Yang, Yujie; Gu, Shanshan; Zhu, Yi
Abstract : Objective . This evidence mapping is aimed at identifying, summarizing, and analyzing the available evidence on cognitive behavioral therapy (CBT) for neuropathic pain (NP). Methods . This study was conducted following the methodology of Global Evidence Mapping (GEM). Searches were conducted in PubMed, Embase, the Cochrane Library, and PsycINFO to identify systematic reviews (SRs) with or without meta-analysis published before February 15, 2022. The authors independently assessed eligibility, extracted data, and evaluated the methodological quality of the included SRs using AMSTAR-2. The results were presented in the tables and a bubble plot based on the identified population-intervention-comparison-outcome (PICO) questions. Results . A total of 34 SRs met the eligibility criteria. According to the AMSTAR-2, 2 SRs were rated "high, " 2 SRs were rated "moderate, " 6 SRs were rated "low, " and 24 SRs were rated "critically low." The most common study design utilized to evaluate the efficacy of CBT for NP was the randomized controlled trial. In total, 24 PICOs were identified. Migraine was the most studied population. CBT for NP usually reaches the "potentially better" result at follow-up. Conclusions . Evidence mapping is a useful way to present existing evidence. Currently, the existing evidence on CBT for NP is limited. Overall, the methodological quality of the included SRs was low. Further improvements in the methodological quality of SRs and more research on the most efficient CBT formats for NP are recommended in the future.